FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Linda Santioso (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract – This study aims to analyze the effect of good corporate governance, capital adequacy ratios, and Indonesian bank interest rates on company financial performance. This study used a purposive sampling method with 31 banking companies listed on the Indonesia Stock Exchange in 2018-2020. The Smart Pls 3.0 application is used in this study’s data processing. The results of this study indicate that good corporate governance has a positive and significant effect on financial performance, the capital adequacy ratio has a positive but not significant effect on financial performance, and Indonesian banking interest rates have a negative but not significant effect on financial performance. In managing banking companies, trust plays an important role where through good corporate governance investors believe that their investments can be protected and investor rights can be properly maintained. In addition, through the adequacy of capital owned by banks, when there is an economic shock, even if they experience a loss, banking companies can still survive to bear losses, this has been proven when the Covid 19 pandemic hit, Indonesian banking companies could survive and even still grow well. Policies or regulations require that when transactions between customers and banks such as loans, deposit openings, interest rates on savings always include if there is a change in Indonesian bank interest rates, all transactions will change accordingly so that the financial performance of the banking sector does not have a major influence on Indonesian bank interest rate policy. Keywords: Financial Performance; Good Corporate Governance; Capital Adequacy Ratio; Indonesian Bank Interest Rate